Equations with fractions
x(x+1) - 4(2x-1) = 1(4)(x+1)
x^2 + x - 8x - 4 = 4x + 4
x^2 + x - 8x - 4 - 4x - 4 = 0
x^2 - 11x - 8 = 0
From there I factorise it to get the answer, but the answer it's supposed to be is 0 , 11
I can't see how that would work out unless it's just x^2 - 11x I think there may be a problem with the fours maybe but I'm not sure.
See the comment in red, x^2-11x=0 is the correct expression and should be easy to solve for the given solutions
Originally Posted by zyx.gar
Yeah I see what I've done there I had it all out of order on my pad. Thanks.